Effects of ACE inhibitors and angiotensin receptor blockers: protocol for a UK cohort study using routinely collected electronic health records with validation against the ONTARGET trial - Baptiste, Paris J.; Wong, Angel Y.S.; Schultze, Anna; Cunnington, Marianne; Mann, Johannes; Clase, Catherine; Leyrat, Clémence; Tomlinson, Laurie A.; Wing, Kevin (BMJ Open, 2022)
INTRODUCTION: Cardiovascular disease is a leading cause of death globally, responsible for nearly 18 million deaths worldwide in 2017. Medications to reduce the risk of cardiovascular events are prescribed based on evidence from clinical trials which explore treatment effects in an indicated sample of the general population. However, these results may not be fully generalisable because of trial eligibility criteria that generally restrict to younger patients with fewer comorbidities. Therefore, evidence of effectiveness of medications for groups underrepresented in clinical trials such as those aged ≥75 years, from ethnic minority backgrounds or with low kidney function may be limited.Using individual anonymised data from the Ongoing Telmisartan Alone and the Ramipril Global Endpoint Trial (ONTARGET) trial, in collaboration with the original trial investigators, we aim to investigate clinical trial replicability within a real-world setting in the area of cardiovascular disease. If the original trial results are replicable, we will estimate treatment effects and risk in groups underrepresented and excluded from the original clinical trial. METHODS AND ANALYSIS: We will develop a cohort analogous to the ONTARGET trial within the Clinical Practice Research Datalink between 1 January 2001 and 31 July 2019 using the trial eligibility criteria and propensity score matching. The primary outcome is a composite of cardiovascular death, non-fatal myocardial infarction, non-fatal stroke and hospitalisation for congestive heart failure. If results from the cohort study fall within pre-specified limits, we will expand the cohort to include under represented and excluded groups. ETHICS AND DISSEMINATION: Ethical approval has been granted by the London School of Hygiene & Tropical Medicine Ethics Committee (Ref: 22658). The study has been approved by the Independent Scientific Advisory Committee of the UK Medicines and Healthcare Products Regulatory Agency (protocol no. 20_012). Access to the individual patient data from the ONTARGET trial was obtained by the trial investigators. Findings will be submitted to peer-reviewed journals and presented at conferences.
CRIS-Team Scopus Importer:2022-03-18
Keywords: clinical trials; epidemiology; statistics & research methods; vascular medicine